(untitled) (Research, Society and Development, 2022)
Objective: To verify if there is a disturbance in the autoregulation of intracranial compliance in patients with chronic kidney disease (CKD), when they have altered blood pressure (BP). Methodology: Intracranial pressure (ICP) monitoring was performed in patients with chronic kidney disease using a non-invasive sensor, developed by the company Brain4care®. Data from monitored patients were statistically analyzed and the correlation between ICP parameters with blood pressure (BP) and beats per minute (BPM), correlation between glomerular filtration with BP and BPM, and comparison between CKD groups in in relation to BP, BPM and PIC. Results: There was no difference between the stages of CKD, and there was no correlation between ICP (ratio P2/P1 and TTP) and BP. However, there was a strong correlation between systolic (SBP) and diastolic (SBD) pressures and ICP parameters. Conclusion: As there was a strong correlation between systolic and diastolic pressures and ICP parameters, there’s evidence of impairment in intracranial compliance in these patients, showing that CKD patients have their homeostasis impaired in the presence of SAH.